Predicting cavitating propeller noise in off-design conditions using scale-resolving CFD simulations. (15th June 2022) - Lidtke, Artur K.; Lloyd, Thomas; Lafeber, Frans Hendrik; Bosschers, Johan
Abstract: There is increasing awareness about the harmful impact of underwater radiated noise of shipping on the marine environment, with propeller cavitation being a major contributor thereof. In order to allow low-noise propeller design, reliable and validated numerical tools are necessary. The combined use of viscous computational fluid dynamics (CFD) and Ffowcs Williams–Hawkings acoustic analogy has long been suggested as a potential frontrunner that could address this need. However, few studies presented in the open literature have shown detailed validation focused on farfield radiated noise of propellers in cavitating conditions. Present work aims to address this by applying the methodology to two thrusters operating in off-design conditions and tested at model scale. Flow is computed using scale-resolving CFD simulations and a mass-transfer cavitation model. This allows for part of the turbulence spectrum and cavitation dynamics to be resolved. It is shown that peak sound pressure levels, corresponding to the low-frequency underwater radiated noise source, may be predicted to within 5 dB of experimental results. In addition, key features of the noise spectra, such as centre frequency of the peak broadband noise level and decay slope, are also well represented in the computations. The results are supplemented by analysis of the numerical signal-to-noise ratio. Highlights: DES and FW-H analogy are used to predict noise of propellers in off-design conditions Present model suffices for predicting large-scale cavitation and low-frequency noise. Noise spectra are validated showing overall good agreement between with experiments. Future inclusion of sub-grid bubbles is needed to improve broadband noise predictions. Improved modelling of cavitating tip vortex dynamics is also desirable.